Studying gaming literacies : theories to inform classroom practice - Garcia, Antero; Witte, Shelbie; Dail, Jennifer S. (Gaming ecologies & pedagogies series,, 2020)
"Recognizing the vast numbers of old and young people alike that interact, socialize, and learn through gameplay, this book explores research approaches to games, their literacies, and the pedagogical possibilities of play. Consequentially, this volume is rooted in the idea that powerful forms of learning, communication, and multimodal production occur through and because of gaming. These profound literacy practices can mirror traditional literacies but the educational field's approach to engaging in a pedagogy of playful literacies has been largely scattershot. By bringing together diverse voices, contexts, and research designs, the chapters in this volume present a snapshot of 21st century literacy practices at work and at play. Organized into two parts, Studying Gaming Literacies explores the rich methodological approaches to gaming literacies scholarship as well as the possibilities of engaging in research in both classrooms and informal learning settings. With a robust set of context-specific approaches, this book acts less as a how-to manual for equity-driven scholarship than as a companion to support and undergird other research and pedagogical approaches to play and gaming in literacy-rich learning environments"--